The role of MAIDAM in managing muslim reverts through dialogue of life aproaching = Peranan maidam dalam pengurusan saudara baru melalui pendekatan dialog kehidupan - Awang, A.; Hambali, K.M. (Kolej University Islam Sultan Azlan Shah, 2016)
Majlis Agama Islam and Malay Customs Terengganu (MAIDAM ) is fully responsible for the management of New Muslims. Mind, emotions and feelings management amongs New Muslims have affected relations with non- Muslim family. Thus, intellectual development through the dialogue of life is meant to correct any misconceptions, handle any situation and promote a harmonious relationship between the two parties. This study was designed to determine the MAIDAM 's role in managing the problems through implementing a dialogue of life. The quantitative methods used to determine the perception of Muslim reverts through dialogue of life in managing religious misunderstanding between Muslim reverts community with family members. Using SPSS 20, the data were analyzed using mean and percentage. The results showed that the perception of Muslim reverts to the role of MAIDAM in building the relations between Muslims and non-Muslim which based on a dialogue of life is at the medium level. Even so, the findings showed the majority of respondents believe that the implementation of the dialogue of life can generate good relations with non- Muslim families.